Serotonergic Dysfunction in Parkinson's Disease and Its Relevance to Disability - Marios Politis; Clare Loane (The Scientific World Journal)
Growing evidence suggests that Parkinson's disease is not solely affecting the dopaminergic system. Results from biochemical, animal, postmortem, and functional imaging studies have revealed that other neurotransmitter systems are affected as well, including the serotonergic system. With the use of in vivo positron emission tomography functional imaging, it has been shown that serotonergic terminals are affected at a varying, nonlinear degree starting early in the clinical course of Parkinson's disease. Tremor and the majority of nonmotor symptoms do not seem to respond adequately to dopaminergic medication. Recent studies suggest that serotonergic dysfunction has a direct relevance to Parkinson's disease symptoms, the so-called nonmotor symptoms, including depression, fatigue, weight changes, and visual hallucinations. These in vivo findings indicate that agents acting on the serotonergic system could help towards alleviating these symptoms. This paper aims to review the current literature and to highlight the need for further in vivo investigations.